A sensitive and high-throughput LC-ESI-MS/MS method to detect budesonide in human plasma: application to an evaluation of pharmacokinetics of budesonide intranasal formulations with and without charcoal-block in healthy volunteers. (1st February 2021) - Li, Xin; Tong, Huan; Xu, Bing; Deng, Yang; Li, Yuan; Huang, Junchen; Mao, Yong; Liu, Mengqin; Zhang, Ping; Guo, Siwei
Abstract: Budesonide is one of the intranasal corticosteroids, referred as first-line therapy for allergic rhinitis. Its determination is a challenging task due to its extremely low plasma levels, which limits the progress in the investigation of pharmacokinetics and quality control of preparations. In this study, a sensitive and high-throughput method to determine budesonide in human plasma using budesonide-d8 as the internal standard was developed and validated. A small volume of plasma sample (0.2 mL) was diluted with 0.2 mL water, followed by a solid-phase extraction using Cleanert PEP-2 products. Extracted samples were analyzed by liquid chromatography coupled to electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). Chromatographic separation of analytes was performed on an InertSustain AQ-C18 HP column (3 µm, 2.1 × 50 mm) under the reversed-phase condition with gradient elution. With the assay, linear calibration curves were obtained over the concentration range of 10–1200 pg/mL for budesonide, with considerable extraction recoveries (84.7–89.4%), and negligible matrix effects (<4.1). Moreover, the newly developed method was successfully applied to the evaluation of pharmacokinetics of two budesonide intranasal formulations with and without charcoal block in healthy volunteers.